Siren Song: A Suspense Novel - Schwandt, Stephen (Bridgeworks, 2004)
JP Griffin buys a small cabin cruiser and plans a carefree summer of boating on the waters surrounding Wisconsin's Door County peninsula, to escape the pain of a failed marriage. He learns the boat he purchased previously was owned by a respected Green Bay cop who had just been killed in a car crash, and learns the boat is full of dark secrets.